Natural microbial communities supporting the transfer of the IncP-1β plasmid pB10 exhibit a higher initial content of plasmids from the same incompatibility group - Bellanger, Xavier; Guilloteau, Hélène; Breuil, Bérengère; Merlin, Christophe (Frontiers in Microbiology, 2014)
Antibiotic resistance gene transfer mediated by plasmids is a matter of concern for public health, but permissive environments supporting plasmid dissemination are still quite difficult to identify. Lately, we have reported a molecular approach based on quantitative PCR to monitor the fate of the IncP-1β plasmid pB10 in natural microbial communities maintained in microcosms. Such plasmid transfer experiments were carried out with 13 different environmental matrices, and demonstrated that the transfer of the conjugative-proficient plasmid pB10 in complex environments is relatively rare and is strongly matrix dependent. An attempt to link the microbial community structure and the matrix permissiveness showed that TTGE analysis is not resolutive enough to point out common features among comparable communities supporting pB10 transfer. However, an estimation of the IncP-1α/IncP-1β plasmids abundance by quantitative PCR demonstrated that pB10 transfer tends to be supported by environmental matrices exhibiting a higher content of IncP-1 plasmids. We suggest that the relative abundance of IncP-1 plasmids in a given microbial community reflects its permissiveness to the transfer of plasmids belonging to the same incompatibility group, which prevails over transfer limitation due to a phenomenon known as superinfection immunity.